2016
DOI: 10.1016/j.vas.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The potential of blue lupins as a protein source, in the diets of laying hens

Abstract: Layers diets typically contain 15–20% soya due to its high crude protein content (ca. 36%). Reliance on soya for protein can result in large increases in cost of feed due to the law of supply and demand as a global commodity. Lupin grains have high protein content (35–40%) but previous experience with white lupins has shown toxic effects in poultry due to high levels alkaloids and poor performance due to anti-nutritional Non-starch polysaccharides (NSP). Here blue lupins either processed or whole were trialled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 25 publications
(38 reference statements)
6
29
0
1
Order By: Relevance
“…In the literature, blue lupine can be incorporated in broilers' diets in up to 25% of soybean meal protein and yield similar results to the soybean meal (16,18) and white lupine diets (21,22). Other researchers found that when blue lupine is fed at 30% of soybean meal protein (19,40,49) and 15% it does not have any negative influences on the production performance and health of layers (8), but increasing blue lupine to 40 and 80% of soybean meal protein decreased growth and impaired gut ecosystem and increased wet dropping (18,19). Similar results were obtained with the inclusion of 25-30% of blue lupine in turkey diets (40,49).…”
Section: Growth Performancementioning
confidence: 84%
See 2 more Smart Citations
“…In the literature, blue lupine can be incorporated in broilers' diets in up to 25% of soybean meal protein and yield similar results to the soybean meal (16,18) and white lupine diets (21,22). Other researchers found that when blue lupine is fed at 30% of soybean meal protein (19,40,49) and 15% it does not have any negative influences on the production performance and health of layers (8), but increasing blue lupine to 40 and 80% of soybean meal protein decreased growth and impaired gut ecosystem and increased wet dropping (18,19). Similar results were obtained with the inclusion of 25-30% of blue lupine in turkey diets (40,49).…”
Section: Growth Performancementioning
confidence: 84%
“…One of the most important strategies for the poultry industry is to develop domestic dietary formulations, which will allow the use of local ingredients as substitutes for imported feed ingredients and, subsequently, reduce diet costs. Legume seeds such as the blue lupine (Lupinus angustifolius), which belongs to the family Fabaceae, are important sources of protein for monogastric animals and are considered as alternatives to the soybean meal (7,8). Blue lupine is characterized by its year-round availability and its low price compared to soybean meal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hull, which constitutes up to 25% of the lupine seeds, contains many compounds (e.g. 65% of cellulose and lignin) that affect the digestibility of the seeds and their protein (Mateos et al , ; Leea et al , ; Mera‐Zúñiga et al , ). However, not only the hull fibre influences digestibility of the lupine protein.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that, while the legumes improved meat quality, poultry demonstrated lower feed conversion ratios and reduced weight gain, suggesting that forages may not be an efficient feed source for broilers. A later study demonstrated, however, that this negative effect can be partially offset by providing exogenous enzymes to utilize fiber and nonstructural polysaccharides (Lee et al., 2016). …”
Section: Effects Of Farming Systems On Meat Qualitymentioning
confidence: 99%